Effects of Text Content and Beliefs on Informal Argument Evaluation. Issue 5 (4th July 2017) - Wolfe, Michael B.; Williams, Todd J.
ABSTRACT: We examined the influence of reading a one-sided text on informal argument evaluation. After reporting initial beliefs in a separate online prescreening, subjects with polarized beliefs read a belief-consistent or -inconsistent text about the benefits of spanking children as a means of discipline. After reading, subjects reported their beliefs and judged the soundness of a series of one-sentence informal arguments that made belief-consistent or -inconsistent claims. Subjects were more likely to accept arguments as sound when the claims were consistent with the position of the text they read and reject them as unsound when the claims were inconsistent with the text position. Process mediation modeling revealed that text position (pro vs. con) influenced reasoning biases both directly and indirectly via the extent to which they experienced belief change. These findings suggest that informal reasoning biases can be malleable and are influenced by both text content and by subjects' beliefs at the time of reasoning.